Research of the purification process of farmland oil-containing water - Прасолов, Евгений Яковлевич; Ломига, Артур Юрійович (Technology audit and production reserves, 2014)
The feasibility of oil-containing water purification by secondary emulsification is grounded to reduce contamination of groundwater in agricultural bases of fuels and lubricants and in the surrounding areas. The laboratory unit and research method of oil-containing water purification are developed. According to the results of experimental researches it is determined the optimal structural and operating parameters of unit for oil-contained water purification. The dependence of oil-containing waterpurification efficiency by the combination of methods of coalescence and liquid filtration from the concentration of oil products, surfactant and water salinity is determined. The principles for design of water purification equipment, the principle of which is based on a combination of coalescence, liquid filtration and the action of electric field are proposed. The process flow sheet of farmland oil-containing water purification is proposed. Implementation of the research results will reduce the negative impact of human factors in the use of agricultural land.